Isolation and partial characterization of extracellular NADPH-dependent phenol hydroxylase oxidizing phenol to catechol in Comamonas testosteroni - Turek, Michal; Vilimkova, Lenka; Kremlackova, Veronika; Paca, Jan; Halecky, Martin; Paca, Jan; Stiborova, Marie (Neuro endocrinology letters, 2011)
OBJECTIVE: Comamonas testosteroni Pb50 is a microorganism that possesses high tolerance for phenol and shows strong phenol degrading activity. This bacterial strain is capable of utilizing phenol as the sole carbon and energy source. Although examples are known in which the C. testosteroni utilizes phenol for growth or metabolism, much less information are known on the nature of the phenol-oxidizing enzymes in this microorganism. Therefore, the occurrence and cellular location of phenol hydroxylase (EC 1.14.13.7), the enzyme participating in the first step of phenol degradation, catalyzing its hydroxylation to catechol in a bacterial Comamonas testosteroni Pb50 strain grown in the presence of phenol as a sole carbon and energy source are the aims of this study. METHODS: Combination of fractionation with polyethylene glycol 6000 and gel permeation chromatography on columns of Sepharose 4B and Sephacryl S-300 was used for isolation of phenol hydroxylase detectable in the medium in which C. testosteroni was cultivated. The sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and gel chromatography on Sephacryl S-300 were used to evaluate the molecular mass of the enzyme. The enzyme activity was followed by HPLC (phenol consumption and/or catechol formation). RESULTS: Whereas low activity of phenol hydroxylase was detected in cytosol isolated from C. testosteroni, more than 16-fold higher activity of this enzyme was found in the medium in which C. testosteroni was cultivated. The presence of phenol hydroxylase extracellular activity suggests that this microorganism may secrete the enzyme into the extracellular medium. Using the procedure consisting of fractionation with polyethylene glycol 6000 and gel permeation chromatography on columns of Sepharose 4B and Sephacryl S-300, the enzyme was isolated from the medium to homogeneity. The formation of catechol mediated by purified phenol hydroxylase is strictly dependent on the presence of NADPH, which indicates that this enzyme is the NADPH-dependent phenol hydroxylase. The enzyme is a homotetramer having a molecular mass of 240 000, consisting of four subunits having a molecular mass of 60 000. The optimum pH of the enzyme for the phenol oxidation is pH 7.6. CONCLUSION: The results are the first report showing isolation and partial characterization of extracellular NADPH-dependent phenol hydroxylase of a bacterial C. testosteroni Pb50 strain capable of oxidizing phenol to catechol. The data demonstrate the progress in resolving the enzymes responsible for the first step of phenol degradation by bacteria.
Keywords: Electrophoresis, Polyacrylamide Gel; extracelulární prostor; Catalysis; Hydrogen-Ion Concentration; katecholy; katalýza; Extracellular Space; fenol; vysokoúčinná kapalinová chromatografie; Time Factors; časové faktory; Catechols; Phenol; Mixed Function Oxygenases; Comamonas testosteroni; oxidace-redukce; Chromatography, High Pressure Liquid; Cloning, Molecular; Oxidation-Reduction; NADP; klonování DNA; elektroforéza v polyakrylamidovém gelu; koncentrace vodíkových iontů; oxygenasy se smíšenou funkcí